2000
DOI: 10.1021/jo000638t
|View full text |Cite
|
Sign up to set email alerts
|

Practical and Highly Enantioselective Ring Opening of Cyclic Meso-Anhydrides Mediated by Cinchona Alkaloids

Abstract: The cinchona alkaloid-mediated opening of prochiral cyclic anhydrides in the presence of methanol leading to optically active hemiesters is described. Very structurally diverse anhydrides are converted into their corresponding methyl monoesters, and either enantiomer can be obtained with up to 99% ee by using quinine or quinidine as directing additive. After the reaction, the alkaloids can be recovered almost quantitatively and reused without loss of enantioselectivity. Additionally, a catalytic protocol which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(77 citation statements)
references
References 65 publications
0
70
0
1
Order By: Relevance
“…The alkaloid could be used at 10 mol% loading in conjunction with stoichiometric amounts of a tertiary amine at -55°C; however, low temperatures and long reaction times (6 d) were necessary. 65 Deng and co-workers later reported that the commercially available, modified cinchona alkaloid (DHQD) 2 AQN and its quinine-derived pseudo-enantiomer could promote the highly enantioselective alcoholysis of succinic anhydride derivatives at 5-20 mol% loading without the need for an added stoichiometric base at temperatures of -20 to -30°C (Scheme 15). The methanolysis of glutaric anhydrides involved the use of higher catalyst loadings of 30 mol% and reactions at -40°C.…”
Section: Meso-anhydride Desymmetrisationmentioning
confidence: 99%
“…The alkaloid could be used at 10 mol% loading in conjunction with stoichiometric amounts of a tertiary amine at -55°C; however, low temperatures and long reaction times (6 d) were necessary. 65 Deng and co-workers later reported that the commercially available, modified cinchona alkaloid (DHQD) 2 AQN and its quinine-derived pseudo-enantiomer could promote the highly enantioselective alcoholysis of succinic anhydride derivatives at 5-20 mol% loading without the need for an added stoichiometric base at temperatures of -20 to -30°C (Scheme 15). The methanolysis of glutaric anhydrides involved the use of higher catalyst loadings of 30 mol% and reactions at -40°C.…”
Section: Meso-anhydride Desymmetrisationmentioning
confidence: 99%
“…[13] A range of meso cyclic anhydrides underwent ADS to give methyl hemiesters in 61 ± 99 % yield and 85 ± 99 % ee with 3 equivalents of MeOH in toluene:CCl 4 (1:1) at À 55 8C within 60 hours (Scheme 1). Under these conditions, quinine provided the antipodal products with comparable enantioselectivities (75 ± 99 % ee).…”
Section: Catalysis Of the Asymmetric Desymmetrization Of Cyclic Anhydmentioning
confidence: 99%
“…To obtain the opposite enantiomer quinine could have been used as the catalyst. 7 The selective reduction of acid ester 10 using Super-Hydride ® 45 furnished lactone 11. 8 Partial reduction of 11 using DIBAL-H gave a lactol which underwent Wittig methylenation to yield alcohol 12.…”
mentioning
confidence: 99%